2020
DOI: 10.3174/ajnr.a6610
|View full text |Cite
|
Sign up to set email alerts
|

Brain Imaging Use and Findings in COVID-19: A Single Academic Center Experience in the Epicenter of Disease in the United States

Abstract: Coronavirus disease 2019 (COVID-19) is a serious public health crisis and can have neurologic manifestations. This is a retrospective observational case series performed March 1-31, 2020, at New York University Langone Medical Center campuses. Clinical and imaging data were extracted, reviewed, and analyzed. Two hundred forty-two patients with COVID-19 underwent CT or MRI of the brain within 2 weeks after the positive result of viral testing (mean age, 68.7 6 16.5 years; 150 men/92 women [62.0%/38.0%]). The 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
144
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(160 citation statements)
references
References 13 publications
11
144
3
2
Order By: Relevance
“…An updated literature search for studies published between July 30, 2020 and October 9, 2020 resulted in 346 studies, of which seven studies met the same eligibility criteria [ [27] , [28] , [29] , [30] , [31] , [32] , [33] ]. Overall, 21 articles with a total of 2125 patients were included [ 4 , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ]. No additional eligible study was found after a search of references within the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An updated literature search for studies published between July 30, 2020 and October 9, 2020 resulted in 346 studies, of which seven studies met the same eligibility criteria [ [27] , [28] , [29] , [30] , [31] , [32] , [33] ]. Overall, 21 articles with a total of 2125 patients were included [ 4 , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ]. No additional eligible study was found after a search of references within the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 21 studies, all study designs were retrospective, except for two prospective studies [ 28 , 39 ]. Nine studies were multi-center studies [ 4 , 29 , 31 , 33 , 36 , 38 , 40 , 42 , 43 ] whereas the other 12 were performed at single centers [ 27 , 28 , 30 , 32 , 34 , 35 , 37 , 39 , 41 , [44] , [45] , [46] ]. The cohort sizes ranged from 9 to 454 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Although initial reports of brain imaging findings in patients with COVID-19 showed ischemic and hemorrhagic complications ( 2 , 5 ), there are now increasing reports of other findings such as patchy demyelinating lesions ( 6 ) and acute hemorrhagic necrotizing encephalopathy involving the thalami and medial temporal lobes ( 3 ). Our report comprises 11 patients in a single 3-week period in April 2020, with all patients having been critically ill and on mechanical ventilation for a mean duration of 26.5 days.…”
Section: Discussionmentioning
confidence: 99%
“…We believe the diffuse leukoencephalopathy and microhemorrhages described herein are late complications of critically ill patients with COVID-19 and likely related to hypoxemia. Previously, we reported brain imaging findings in 242 consecutive patients with COVID-19 seen at our institution in March 2020 ( 2 ). None of those patients demonstrated these diffuse patterns of white matter involvement that we describe here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation